Development of Biocompatible and Antibacterial Collagen Hydrogels via Dialdehyde Polysaccharide Modification and Tetracycline Hydrochloride Loading. Issue 5 (22nd March 2019) - Yu, Xiaoyue; Yuan, Qijuan; Yang, Mingtao; Liu, Ru; Zhu, Shichen; Li, Jinling; Zhang, Wanni; You, Juan; Xiong, Shanbai; Hu, Yang
Abstract: Nowadays, collagen hydrogels with both good physicochemical and antibacterial properties for tissue engineering have drawn broad attention. Herein, a biocompatible and antibacterial collagen hydrogel is developed via alginate dialdehyde (ADA) modification and tetracycline hydrochloride (TC) loading based on Schiff's base formation. Fourier transform infrared spectroscopy and X‐ray diffraction spectra suggest the maintenance of collagen structure integrity after ADA modification. The modification significantly contributes to the improved swelling property, resistance against type I collagenase, and strengthens storage modulus of hydrogels with an increase of ADA concentrations. Meanwhile, dynamic release curves of tetracycline hydrochloride (TC)‐loaded hydrogels describe the burst release at the first 15 min then a gradual release, hydrogels act ideally as carriers in antibacterial activity. Furthermore, in vitro biocompatibility and antibacterial properties are successfully confirmed from the fabricated collagen hydrogels. This physicochemical‐ and antibacterial‐property–improved collagen hydrogel would be a potential candidate for wound healing as a scaffold. Abstract : Collagen hydrogels, derived from fish skin, with improved physicochemical properties (e.g., swelling behavior, resistance against collagenase type I, storage modulus), ideal biocompatibility, and good antibacterial properties are developed, with dialdehyde alginate operating as cross‐linker and tetracycline hydrochloride (TC) serving as antibacterial agent. This fabricated hydrogel is a potential candidate for wound healing as a scaffold.